Exploring the Constructions of English Teachers’ Professional Identity in Islamic Private Junior High Schools Through Bourdieu and Kelchtermans’ Lenses - Nadiah Ma'mun; Ahdi Riyono; Welliam Hamer (Journal of English Education Studies, 2026)
This study investigates the construction of professional identity among English teachers in Islamic private junior high schools by employing a narrative inquiry approach and drawing on the theoretical frameworks of Pierre Bourdieu and Geert Kelchtermans. Through in-depth life story interviews with selected teachers, the research explores how individual habitus, various forms of capital (Bourdieu), and personal interpretative frameworks (Kelchtermans) shape and are shaped by institutional, cultural, and religious contexts. The study reveals that teachers’ professional identities are not fixed entities but are continuously negotiated and reconstructed through their past experiences, educational paths, values, beliefs, and the socio-religious field in which they work. Teachers’ dispositions toward teaching are deeply embedded in their social backgrounds and influenced by both internal (self-image, mission, task perception) and external (contextual challenges, interpersonal relationships) factors. This research offers insights into how professional identity in Islamic educational settings is shaped by a complex interplay of structure and agency, highlighting the need for context-sensitive professional development that acknowledges teachers’ lived experiences. The findings contribute to the discourse on identity formation in English language teaching by emphasizing narrative, cultural, and reflective dimensions in teacher education.